Studying Sharp Changes of Urban Landscape: Concession Within Agricultural, Hydraulic, and Maritime Public Domain in Kelibia City, Northern Tunisia - Kassouk, Zeineb; Hammami, Hela; Ismail, Haithem (Frontiers in Sustainable Cities, 2022)
Coastal cities are desirable places to live and work which results in ongoing and increasing urbanization. In southern Mediterranean countries, coastal urbanization often occurs on croplands. This expansion is frequently on most productive croplands and emerges as an important sustainability concern. The aim of this study is to quantify urban growth over lands in Kelibia city, a coastal region in Tunisia that is one of the most threatened Mediterranean regions. We describe the changes in urban structures during the period of 2012–2016 by using Multi dates Pleiades images and using Otsu binary and sample-based Edge segmentation. Otsu segmentation showed higher accuracy than Edge segmentation method. Based on Otsu binary maps, urban areas were quantified in two dates. The results illustrated a dramatic increase of urban areas at the expense of agricultural land, maritime public domain (MPD) and hydraulic public domain (HPD). Analysis of parameters for urban sprawl quantification evaluated a sharp increase of urbanization rate, intensity, and dynamic degree. FRAGSTAT metrics described the change of landscape structure due to the increase of fragmentation pace, compactness degree, shape complexity, and proximity reduction. This significant urban change in extent and structure during a short temporal scale could be considered as a serious issue. For this reason, the implementation of systematic strategies for urban monitoring requires citizen awareness, law enforcement, and scientific supervision to mitigate land consumption, reduce flooding vulnerability, and to control the environmental impacts of urbanization.